Kędzierzyn-Koźle – dziedzictwo przeszłości w kulturze miasta przemysłowego na pograniczu etniczno-kulturowym (Politeja, 2022)
Kędzierzyn-Koźle – The Heritage of the Past in the Culture of the Industrial City Functioning in the Ethnic and Cultural FrontierThe article draws attention to the issues of symbolic functioning of the city which was formed of two different entities as a result of political and economic decisions. In the 20th century, the history of a traditional city got entwined with a modernistic industrial city which was taking shape. As a result, ideologies and politics impacted on the newly-established conurbation. The city denotes not only the material sphere, but also its urban community, which, in the case of the places under study, was basically historically complicated. The method of description is the ‘culturalistic’ orientation in the study of the city and also the (emotional) sociology of Silesia of the Rev. Emil Szramek. The author’s reflections touch upon ideas, facts as well as the real city’s organism shaped in its longterm and short-term perspective.